Unusual optical coherence tomography and fundus autofluorescence findings of eclipse retinopathy - Kun-Hsien Li; San-Ni Chen; Jiunn-Feng Hwang; Chun-Ju Lin (Indian Journal of Ophthalmology, 2012)
A 63-year-old female patient complained of dimness in the central field of vision in the left eye after viewing an annular partial eclipse without adequate eye protection on 22 July 2009. Fundoscopy showed a wrinkled macular surface. Fundus autofluorescence study revealed well-demarcated hyperautofluorescence at the fovea. Optical coherence tomography demonstrated tiny intraretinal cysts. Fluorescein angiography and indocyanine green angiography were unremarkable. Epimacular membrane developed in the following month with deteriorated vision. Vitrectomy, epiretinal membrane and internal limiting membrane peeling were performed. Vision was restored to 20/20 after the operation. Direct sun-gazing may damage the retinal structures resulting in macular inflammation and increased focal metabolism, which explains the hyperautofluorescence. It may also induce epimacular membrane. Fundus autofluorescence might represent a useful technique to detect subtle solar-induced injuries of the retina. The visual prognosis is favorable but prevention remains the mainstay of treatment. Public health education is mandatory in reducing visual morbidity.